Clinical manifestation and genetic analysis in Chinese early onset X‐linked retinoschisis - Huang, Li (Mol Genet Genomic Med, 2020)
BACKGROUND: X‐linked retinoschisis (XLRS) is one type of retinal dystrophy leading to the schisis of the neural retina and causing reduced visual acuity. The study aimed to investigate the clinical manifestations and retinoschisin 1 (RS1) mutations in Chinese patients with early onset XLRS. METHODS: Thirty‐eight probands with early onset XLRS were recruited, comprehensive ophthalmic examination was performed. A targeted gene panel was used to test the RS1 mutations. RESULTS: All probands had RS1 hemizygous mutations including 16 known and 14 novel mutations. The median onset age was 2 years old (range 0.1–6 years). Probands with onset age ≤1 years. had more complications (retinal detachment and vitreous hemorrhage, p < 0.001), more mutations outside the discoidin domain and more non‐frameshift mutations than probands with onset age >1 years. Macular and peripheral involvement was present in 77.27% of probands, and inner and outer nuclear layer splitting were present in 53.57% of probands. Electroretinography showed an electronegative waveform. The relatively rare phenotypes of lamellar macular hole and macular hole were present in a unilateral eye in three probands. CONCLUSION: In conclusion, the early onset XLRS developed more severe complications which need close monitoring and clinical manifestations illustrated here may facilitate the early diagnosis of retinoschisis.